The Role of Transition Finance, Renewable Energy Investment, and Climate Risk Management on the Financial Performance of Energy Companies in Indonesia - Sev Rahmiyanti; Iin Wijayanti; Khusnatul Zulva; Arlis Dewi Kuraesin; Kristanti Rahman (West Science Social and Humanities Studies, 2026)
This study examines the role of transition financing, renewable energy investment, and climate risk management in influencing the financial performance of energy companies in Indonesia amid the global transition toward a low-carbon economy. A quantitative approach was employed using primary data collected from 75 managers and professionals in the energy sector through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using SPSS version 25 through descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that transition financing has a positive and significant effect on financial performance, suggesting that access to sustainable financing mechanisms supports corporate financial stability during the energy transition. Renewable energy investment also shows a significant positive influence, indicating that investment in clean energy technologies enhances operational efficiency and long-term competitiveness. Furthermore, climate risk management significantly affects financial performance, highlighting the importance of identifying and mitigating climate-related risks to maintain corporate financial resilience. Simultaneously, the three variables significantly influence financial performance with an R² value of 0.480, indicating that 48% of the variation in financial performance can be explained by the model. These findings demonstrate that the integration of sustainable financial strategies and environmental risk management practices can improve the financial performance of energy companies, while also contributing empirical evidence to the literature on climate finance and corporate sustainability and offering practical insights for managers, investors, and policymakers in supporting the transition toward sustainable energy systems.